Peningkatan Pemahaman Demokrasi Dalam Menghadapi Pemilu Bagi Generasi Muda Pada Program Studi PPKn di Universitas Abulyatama - Asih Winarty; Akhyar Akhyar; Hasanah Hasanah; Silvi Puspa Widya Lubis; Muhammad Hadid Al Hafitz (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
This article is intended to explain the increasing understanding of democracy in dealing with elections for the younger generation. The method used is qualitative with a phenomenological approach. Abulyatama University was used as the object of research. The source of the data was obtained from the students of the University of Abulyatama, the PPKn Study Program. Collecting data using interviews, observation, and documentation. Implementation of increasing understanding of democracy in dealing with elections for the younger generation through four steps, namely planning, implementation, monitoring, and evaluation. The four steps in increasing understanding of democracy in facing elections for the younger generation at Abulyatama University have been carried out well. There is one step that needs to be implemented in order to increase understanding of democracy in dealing with elections for the younger generation at Abulyatama University, namely conducting a consultation stage for students of the Civics Study Program. If this application is not able to find a solution, then the reverse pattern is applied, namely from the PPKn study program lecturers